Intergenerational equity based optimization model joint of water allocation and water quality management - Chunlan Lv; Yanli Chen; Qian Huang (Scientific Reports)
Abstract Global warming and the excessive exploitation of water resources have raised significant concerns regarding water scarcity and the degradation of aquatic ecosystems. To enhance integrated water resource management, a multi-objective optimization model integrated water allocation and water quality has been developed, in which there are trades-off between average economic benefit efficiency maximization and social welfare for long-term sustainability. In the social welfare maximization objective, an adapted Bentham–Rawls criterion is incorporated to addresses intergenerational trade-offs in high-quality water resource allocation, and the overlapping generations structure is employed to analyze the intertemporal dynamics of water pollution, thereby alleviating the conflicts between economic growth and environmental quality in the basin. Besides, total economic efficiency maximization objective is also important as it ensures the effective utilization of water resources. Using the heavily polluted Tuojiang River basin in China as a case study, the feasibility and rationality of this model have been demonstrated. Scenario analysis further validates the model’s effectiveness and explores the impacts of varying control parameters. Results indicate that improving sewage treatment capacity, reducing water pollution accumulation, and accounting for the reasonable needs of future generations for high-quality water can promote the sustainable development of the basin. Compared with the previous models, the proposed optimization model is capable to increase the social welfare by 13.83% and total economic efficiency by 15.97%.